TENDER OFFER PRACTICES AND IMPLEMENTATION OF THE COMPULSORY TENDER OFFER OF PT. MULIA BOGA RAYA TBK BY PT. GARUDAFOOD PUTRA PUTRI JAYA TBK - Erlangga, Jati (Cepalo, 2023)
The issue of tender offers has surfaced, among others, because there have been several cases of takeovers of public companies by other parties, causing losses to other shareholders, especially public shareholders. The main issues to be discussed, namely how the regulation of Tender Offers in Indonesia, what are the legal consequences of Tender Offers. This research aims to find out the regulation of Tender Offer in Indonesia and the impact of Take Over on Public Companies that are taken over. The form of research in writing this journal is a normative legal research jurisdiction using a statutory approach. The results in this research. The regulations regarding takeovers and tender offers are contained in Law Number 8 of 1995 concerning the Capital Market and Government Regulation number 27 of 1998. the result of this study is that in 2011 the Government passed Law Number 21 of 2011 concerning the Financial Services Authority which resulted in the transfer of power regarding macroeconomic regulation from Bank Indonesia to OJK which includes the Take Over and Tender Offer process. In 2020 PT Garudafood Putra Putri Jaya, Tbk. Did a Takeover (Take Over) to PT Mulia Boga Raya, Tbk.